MEMBANGUN DESA DENGAN EDUKASI SAINS DAN TEKNOLOGI MELALUI PROGRAM KULIAH KERJA NYATA (KUKERTA) DI KELURAHAN MUNCUL KOTA TANGERANG SELATAN - Sihabbudin, Firman; Maulidah, Amelia; Rahmadhani, Az Zahra; Sabila, Ardelia Nur; Amaliyah, Fina Fitratun (Sekolah Tinggi Ilmu Ekonomi AMA, 2026)
Kuliah Kerja Nyata (KUKERTA) is a community engagement initiative based on the Tri Dharma of Higher Education, aiming to raise public awareness about the importance of science and technology. This program was conducted in Muncul Subdistrict, South Tangerang, using the Participation Action Research (PAR) method, which involved the community in the planning, implementation, and evaluation of activities. Over a period of approximately 40 days, the program included computer training for local officials, the introduction of basic physics concepts to children, and the distribution of educational booklets. The results indicated improved community understanding of science and technology applications in daily life, increased public participation in educational activities, and strengthened intergenerational collaboration. This program positively impacted science literacy awareness, supported technology-based public services, and fostered a culture of lifelong learning. Through a collaborative approach, this KUKERTA successfully drove social transformation toward sustainable and independent science and technology-based community empowerment.